Clinical profiles and treatment evaluation of tuberculous uveitis in tertiary eye hospital in Jakarta - Mahayani, Ni Made Widya; Susiyanti, Made; Sjamsoe, Soedarman; Utami, Anna Nur (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Tuberculous uveitis (TU) is the second most common cause of intraocular inflammation in Indonesia. This study aimed to determine the clinical characteristics of patients with TU and the therapies used at Jakarta Eye Center (JEC) Eye Hospitals and Clinics. METHODS This retrospective descriptive study included 265 eyes of 189 patients diagnosed with TU at the JEC Eye Hospital and Clinics between January 2018 and June 2022. This study used secondary data collected by reviewing patient medical records, including clinical profiles and therapeutic characteristics recorded during treatment. Data were analyzed using SPSS software version 24 for Windows. RESULTS Most patients (68.3%) complained of blurry vision, and 99 (52.4%) underwent an interferon-gamma release assay. HIV infection was present in 8.5% of the patients, and 4.8% had diabetes mellitus. Among them, 27 (14.3%) had posterior uveitis, 34 (18.0%) had anterior uveitis, and 127 (67.2%) had panuveitis. The most common feature of inflammation was vitreous opacity. Visual acuity (VA) improved to 0.4 (1.11) after treatment. The most common complication was cataract formation (71 patients). In the group that received combination therapy with systemic steroids and anti-tuberculosis treatment (ATT), 58.7% had a better VA. CONCLUSIONS TU has several clinical manifestations. Treatment with systemic steroids, ATT, or a combination of both can improve VA.